A Primer on the Military Health System's Approach to Medical Research and Development. (November 2020) - Rasmussen, Todd E.; Kellermann, Arthur L.; Rauch, Terry M.
Abstract : The Military Health System (MHS) has a medical research program aimed at a wide range of health-, disease-, and injury-related topic areas that works with civilian academic institutions and the biomedical industry to accomplish its goals. There are many opportunities for civilian academic institutions and the biomedical industry to engage with this program, but its unique features are important to understand to optimize the chances for successful partnerships. Unlike the National Institutes of Health, which uses an "investigator-initiated" approach, the Department of Defense (DoD) aligns its funding with specific needs, also referred to as requirements; thus, DoD research is often described as "requirements-driven" research. At the highest level, requirements are aligned with the National Security Strategy and National Defense Strategy, though requirements documents list specific areas in medicine with unmet needs. Military labs and the Uniformed Services University of the Health Sciences, which can also receive DoD appropriations to conduct medical research, serve as hubs that interface with civilian academic institutions and the biomedical industry and organize and track the overall progress of DoD investments. As a mechanism to propel findings from "bench to bedside, " the military budgets funds for the various phases of research and development for a given topic area. Research programs are most effective when they are integrated into the MHS learning health system, which allows MHS clinical communities to inform and track research investments and evaluate the utility of research products in real clinical practice settings. This Perspective provides introductory information and a basic framework for those interested in performing DoD-funded medical research or collaborating with researchers in military labs. It is hoped that as academic institutions and the biomedical industry look to increase efficiency in medical research, they will find ways to engage with DoD research opportunities and consider elements of the military's approach useful.